Melampaui Kepatuhan: Implementasi Sistem Pemerintahan Berbasis Elektronik sebagai Proses Transformasi Tata Kelola Digital di Provinsi Kalimantan Timur - Irwansyah; Aji Ratna Kusuma; Bambang Irawan (Jurnal Bina Praja, 2025)
The implementation of the Electronic-Based Government System (SPBE) in Indonesia has largely been perceived as an administrative compliance mechanism aligned with national policies and index-based assessments. Conceptually, however, SPBE is intended as an instrument for transforming governmental governance toward an integrated, effective, and accountable digital government. This study aims to analyze the implementation of SPBE in East Kalimantan Province by positioning it as a digital governance transformation process rather than merely an administrative obligation. Using a qualitative case study approach, data were collected through policy document analysis, SPBE performance reports, and interviews with key stakeholders within the East Kalimantan Provincial Government. Data were analyzed using a descriptive-analytical method by linking empirical findings to the digital government transformation framework. The findings indicate that SPBE implementation in East Kalimantan Province remains largely compliance-driven, as reflected in institutional fragmentation, limited system and data integration, and uneven human resource capacities across government agencies. Nevertheless, the study also identifies opportunities to strengthen digital governance transformation through reinforcing SPBE institutional governance, enhancing civil servants’ digital competencies, and promoting cross-system and service integration. This study underscores the need to shift the paradigm from administrative compliance toward substantive digital governance transformation at the provincial government level.